Does Inducing Informal Firms to Formalize Make Sense? : Experimental Evidence from Benin - Benhassine, Najy; McKenzie, David; Pouliquen, Victor; Santini, Massimiliano (Elsevier, 2018)
Efforts to bring informal firms into the formal sector are often based on a view that this will bring benefits to the firms themselves, or at least benefit governments through increasing the tax base. A randomized experiment based around the introduction of the entreprenant legal status in Benin is used to test these assumptions, along with supplementary efforts to enhance the presumed benefits of formalizing to firms. Few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales or profits, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness.